Pemantau Gas Metana, Suhu, dan Kelembaban sebagai Penyebab Efek Rumah Kaca Dipadang Lamun Berbasis Internet Of Things - Lukman Medriavin Silalahi; Irfan Kampono; Agus Dendi Rochendi; Muhamad Husni; Raden Sutiadi; Daniel Putra Pardamean Mbarep (KILAT, 2021)
Seagrass is a plant that covers coastal areas/shallow seas that can produce methane gas (CH4) during the decomposition process. The occurrence of decay caused by microbes in seagrass plants that have died in the process produces methane gas (CH4) as the cause of the greenhouse effect. Methane gas monitoring system (CH4) is proposed using MQ-4 sensor, temperature and humidity sensor (DHT11) using NodeMCU ESP8266 module, SD Card module as backup data storage and processed with local database and through mysql database the data will be displayed on the website page for information. . From the tests carried out, the response time for DHT11 is 5.6 seconds and MQ-4 is 1.5 seconds. It has a reading sensitivity rate of 99.92% for DHT11, 99.997% for MQ-4. The accuracy rate for DHT11 is a multiple of 1. For the MQ-4 sensor it has an accuracy level of 2 digits behind the comma. The tool has a data transfer rate of up to that which appears on the front-end 0.2736. With this tool, checking measurement results can be done quickly and can be done from anywhere.